Advances in non-dopaminergic treatments for Parkinson's disease - Stayte, Sandy; Vissel, Bryce (Frontiers in Neuroscience, 2014)
Since the 1960’s treatments for Parkinson's disease (PD) have traditionally been directed to effectively restore or replace dopamine, with L-Dopa the gold standard. However, chronic L-Dopa use is associated with debilitating dyskinesias, limiting its effectiveness. This has created a need to develop new therapies that work in ways other than restoring or replacing dopamine. We provide a comprehensive overview of the emerging non-dopaminergic pharmacological treatments including drugs targeting adenosine, glutamate, adrenergic, and serotonin receptors, as well as GLP-1 agonists, calcium channel blockers, iron chelators, anti-inflammatories, neurotrophic factors and gene therapy, with a detailed overview of their success in animal models and their translation to human clinical trials. We suggest that further developments in the identification of novel therapeutics, particularly those offering disease-modifying effects, will consistently be met with challenges until improvements in clinical trial design and advances in understanding the basic science of PD are made. We consider how developments in genetics, the possibility that PD may consist of multiple disease states, and potential etiology in non-dopaminergic regions will influence drug development. We conclude that despite the challenges ahead patients have much cause for optimism that novel therapeutics that offer better disease management and/or which slow disease progression are inevitable.